Attention Bias Modification in Remitted Depression Is Associated With Increased Interest and Leads to Reduced Adverse Impact of Anxiety Symptoms and Negative Cognition. (May 2019) - Kraft, Brage; Jonassen, Rune; Heeren, Alexandre; Harmer, Catherine; Stiles, Tore; Landrø, Nils Inge
Using a computational network approach, we reanalyzed data from a randomized controlled trial of attention bias modification (ABM) tasks on residual depression symptoms. The main aim was to characterize the symptom-to-symptom changes following ABM. ABM was associated with improvements in interest, which was in turn associated with improvements in other depression symptoms. Although there were no changes in the global network strength following ABM, the comparison with symptom change in the ABM and control group suggests that ABM leads to a reduction of the association between anxiety, depressed mood, and guilt. Findings suggest that reduction in depression symptoms following ABM may have been set in motion by increased interest and involvement in everyday activities, leading to a reduction of the adverse impact of anxiety and negative cognition. ABM may be more effective in patients in whom these symptoms are prominent.